Duolingo: A Qualitative Study on Vocabulary Acquisition - Pramesti, Raisha Dian; Padmadewi, Ni Nyoman; Wahyuni, Luh Gede Eka (STKIP AGAMA HINDU SINGARAJA, 2025)
This qualitative study aims to investigate how the teacher implements the Duolingo application as an English vocabulary learning media and to explore students' opinions on using the Duolingo application in one public high school in Bali. The data in this study were collected through interviews, classroom observation, and questionnaire. The findings show that the teacher integrated the Duolingo application during the activity stage by elaborating on brain warm-up activities adopted from questions, exercises, and material in the Duolingo application. The main activity of using the Duolingo application as a learning medium was divided into several groups, and then the teacher instructed students to work on the learning targets available in Duolingo with sections and units that the teacher had determined. Students reported that learning to use Duolingo provided an engaging and practical experience and helped them improve their vocabulary skills significantly. Students highlight the interactive features of the Duolingo application as motivated and user-friendly, leading to consistent vocabulary learning habits. These findings suggest that integrating Duolingo in the language classrooms can enhance vocabulary and student engagement, offering educators tools to support traditional teaching methods and promote active, self-directed learning.